Thread: GCD question
View Single Post
gimpy
#1
Jan31-04, 02:14 PM
gimpy's Avatar
P: 29
Ok im trying to solve this question.

Assume [tex]n \geq 3[/tex], prove that [tex]gcd(x, n) = gcd(n-x, n)[/tex] for all [tex]0 \leq x \leq n/2[/tex].

This is what i got:

[tex]x = 0[/tex] then [tex]gcd(0, n) = gcd(n-0, n) = n[/tex]

[tex]x = n/2[/tex] then [tex]gcd(n/2, n) = gcd(n-n/2, n) = n/2[/tex]

[tex]0 < x < n/2[/tex] then [tex]x = n/k[/tex] for some [tex]k>2[/tex]

[tex]gcd(n/k, kn/k) = n/k[/tex] because [tex]n = kn/k[/tex]

so [tex]n - n/k = kn/k - n/k = (kn - n)/k = (k-1)n/k[/tex]

therefore [tex]gcd(n-x, n) = gcd((k-1)n/k, kn/k) = n/k[/tex]

therefore [tex]gcd(x, n) = gcd(n-x, n)[/tex]

Im not sure if that is correct but it makes sense to me. Anyways after this qeustion i have to answer this one:

Use the previous question to prove that [tex]\phi(n)[/tex] is an even number. Where [tex]\phi(n)[/tex] is the eurler function.

Im having trouble with this one. Can anyone help me out?
Phys.Org News Partner Science news on Phys.org
'Smart material' chin strap harvests energy from chewing
King Richard III died painfully on battlefield
Capturing ancient Maya sites from both a rat's and a 'bat's eye view'